1983
DOI: 10.1084/jem.157.1.371
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic potential severely altered by changes in tumor cell adhesiveness and cell-surface sialylation.

Abstract: It has been shown recently that high metastatic tumor lines can be converted to low metastatic ones by mutagenization and selection for resistance to toxic concentrations of the lectin wheat germ agglutinin (1-3). Lectin-resistant variants were found to differ from the parental lines and respective revertants in terminal cell-surface carbohydrates. Here we describe for the first time a drug-independent selection procedure for the isolation of a low metastatic variant type cell from a high metastatic tumor line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 8 publications
(9 reference statements)
4
83
0
Order By: Relevance
“…Furthermore, there is substantial evidence that sialic acids are structural determinants for a variety of important cell-cell interactions and cellular functions, such as the adhesiveness and metastatic potential of neoplastic cells (2)(3)(4) and the phenomenon of contact inhibition in tissue culture (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is substantial evidence that sialic acids are structural determinants for a variety of important cell-cell interactions and cellular functions, such as the adhesiveness and metastatic potential of neoplastic cells (2)(3)(4) and the phenomenon of contact inhibition in tissue culture (5).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, O-linked carbohydrate antigens, such as mucin antigen (MUC1), carcinoembryonic antigen (CEA), sialyl LewisX (SLX), CA19-9, Sialyl Tn (STn), and Tn have been reported to be associated with altered adhesion (Fogel et al, 1983;Rice and Bevilacqua, 1989), invasion (Bolscher et al, 1988;Matsushita et al, 1991;Nakamori et al, 1994), recurrence, and prognosis (Itzkowitz et al, 1990;Niklinski et al, 1992;Ogawa et al, 1994;Cao et al, 1995;Diez et al, 1996;Ohgami et al, 1999) in lung cancer and other tumours. Mucin-type O-linked carbohydrates may constitute up to 80% of the total mass of these glycoproteins ; O-glycosylation has been shown to be important in the binding of cell adhesion molecules, cell differentiation, invasion, and metastasis in tumours (Nakamori et al, 1994;Clausen and Bennett, 1996;Sutherlin et al, 1997;Nomoto et al, 1999).…”
mentioning
confidence: 99%
“…1,2 Alterations in sialylation during malignant transformation have been observed to be closely associated with the malignant phenotype in terms of metastatic potential and invasiveness. [3][4][5][6][7] To understand how sialidases are involved in this aberrant sialylation, our study has focused on mammalian forms in cancer cells.Mammalian sialidases are classified into 3 to 4 forms based on their subcellular localization and substrate preference. Cytosolic, lysosomal and membrane forms of the sialidases have been cloned; their primary sequences revealed that they are proteins encoded by distinct genes with different major subcellular locations and enzymatic properties.…”
mentioning
confidence: 99%
“…1,2 Alterations in sialylation during malignant transformation have been observed to be closely associated with the malignant phenotype in terms of metastatic potential and invasiveness. [3][4][5][6][7] To understand how sialidases are involved in this aberrant sialylation, our study has focused on mammalian forms in cancer cells.…”
mentioning
confidence: 99%